Recent progress in silver nanowire based flexible/wearable optoelectronics - Kwon, Jinhyeong; Suh, Young D.; Lee, Jinhwan; Lee, Phillip; Han, Seungyong; Hong, Sukjoon; Yeo, Junyeob; Lee, Habeom; Ko, Seung Hwan (Journal of Materials Chemistry C, 2018)
Among diverse nanomaterials, silver nanowire (AgNW) has reached a certain level of technological maturity, and numerous commercialized AgNW products are already on the market for research and prototype purposes. One of the potential applications for AgNW and its percolative form is in wearable electronics, owing to the superior electrical, optical and mechanical properties that arise from the material itself or the overall interconnected structure. For successful application towards wearable applications, constituent AgNWs should first have uniform and controllable properties. At the same time, it is preferential to develop relevant scalable fabrication processes, together with the verification of potential applications from a proof-of-concept standpoint. Based on these progresses, we summarize the recent developments in AgNW based flexible/wearable optoelectronic applications and foresee their future development.
Keywords: Fabrication process; Interconnected structures; Optical and mechanical properties; Optoelectronic applications; Proof of concept; Recent progress; Silver nanowires; Wearable applications